Lumbar sympathectomy in end stage arterial occlusive disease. - Kim, G E (1976)
Sixty-one patients had lumbar sympathectomies performed for end stage occlusive vascular disease manifested by gangrene of less than one-half of the foot, ulcerating ischemic lesions, rest pain or rapidly progressive markedly limiting intermittent claudication. The operative procedure was standardized to permit removal of the lowermost preganglionic fiber at the level of the crus of the diaphragm and the ganglionated chain to the crossing of the iliac vessels. The immediate postoperative mortality was 6.5% from cardiac causes. Over all improvement rate was 60% while early amputation rate was 40% for the entire group. Those patients with rest pain had the poorest prognosis with an amputation rate of 53%. The results are compared to other groups and factors of patient selection, anatomy of the sympathetic chain in relation to operative technique, physiology of decentralization versus devervation are discussed. The procedure is worthwhile in patients who are not candidates for arterial reconstruction who are faced with the prospect of early amputation.